Dosimetria em pacientes submetidos à varreduras de crânio por tomografia computadorizada - Reginaldo Gonçalves Leão Júnior (2012)
CT scans are widely used today as a method of efficient diagnostic reliable and noninvasive. However, the use of X-ray, to obtain images causes an energy deposit in tissues that can be potentially harmful. Thus, is important to know dosimetric variation profiles obtained in ascanning, they, in addition to providing an indication of the longitudinal dose enable important inferences about the X-ray spectrum at different depths of the swept volume. It can be obtained when it comprises a distribution profile of along a radiochromic film, which darkens so proportional to the energy deposition in your length. The doses are extracted when the values of these profiles integral is compared with the gray levels obtained by another dosimetric method, which in this work was by using a pencil ionization chamber. The simulation of the scanned structure, the human skull, was performed with a cylindrical object compound of polymethylmethacrylate (PMMA). One of several objectives of this study was to build profiles with this feature, for the purpose of describing the scans in terms of its features dosimetric and changes spectrographic introduced by interaction with the PMMA, whose characteristics approaching those own the human skull. These data served as the background for a more significant investigation whichsought to reveal the variations dosimetric scans of the brain when they are done with the gantry maintained perpendicular to the scanning axis or when the gantry is tilted, in order to avoid direct irradiation in the crystalline. In this case, dose reductions were found between the first and second technique on average 89% ou 30 mGy in dosimetric values. Although the dose descriptors are found within the reference levels, it is notable that there is potential for optimization of the technique of head scans, considering that the latter has been abandoned in favor of thetechnique with no gantry tilt since the popularization of MDCT devices with multiplanar fast reconstruction.